Metode Pendokumentasian Elektronik dalam Meningkatkan Kualitas Pelayanan Keperawatan - Sulastri Sulastri; Niken Yuniar Sari (Politeknik Kesehatan Tanjung Karang, 2018)
Nursing documentation is one of the most important functions for nurses in providing nursing care. The nursing process in the modern era is now a demand from various aspects for nurses. The current development is that nurses must carry out nursing processes based on nursing care standards. The use of electronic nursing documentation can always evolve in line with technological developments, this can increase client life expectancy and reduce errors in intervening with clients. This IT-based documentation system will help in meeting documentation standards, can improve the quality of documentation, facilitate decision making and provide information that is easy to access, can minimize the potential for loss or damage to development records, improve information exchange and coordination between nurses or other health teams, documentation can be easily audited, help improve the accuracy of client data, can access the progress of client health development and reduce maintenance costs so that it can improve the quality of care services.